Martial Culture and Historical Martial Arts in Europe and Asia
XXII, 381 p. 267 illus., 230 illus. in color.
Keywords: This open access book is the first publication to provide a comparative framework for the study of martial culture and historical martial arts in Europe and Asia, in particular in Italy and China. Due to the interdisciplinary nature of martial studies, contributors to this volume include historians, archeologists, art historians, scholars of fencing literature, metallurgists, as well as contemporary master swordsmiths and masters-of-arms in historical martial arts. Assembling researchers from these diverse fields, this book offers a multi-perspectival and dynamic view of martial culture across time and space. The cross-cultural and interdisciplinary significance of this book cannot be overemphasized. Whereas a number of contributors are internationally recognized and, indeed, leading authorities in their respective fields; for example, Jeffrey Shaw has been a world-leading new media artist and scholar since the 1970s, while Ma Mingda is a well-known historian and the contemporary founder of Chinese martial studies; and while there are significant overlaps in their research interests, this book brings their research within a single volume for the first time. Equally significant, the book is structured in such a way to reflect the various core aspects of martial studies, particularly in relation to the study of historic sword culture, including history, culture, philosophy, literature and knowledge transmission, material culture, as well as the technical aspects of historical fencing. As one of the first titles on martial studies, this book becomes a reference not only for scholars taking an interest in this subject, but also for historians; scholars with interest in Chinese and/or Italian history (particularly of the Medieval or early modern periods), the history of international relations in Asia / Far East; anthropologists; scholars of martial (arts) studies and researchers in sword-making and/or historic metallurgy.